Effectiveness of Hydrotherapy Interventions for Students with Aquaphobia: A Systematic Review and Meta-Analysis - Santoso, Januar Abdilah; Santoso, Puji (Journal of Educational Sciences, 2025)
This systematic review examines the effectiveness of hydrotherapy interventions for students with aquaphobia across educational settings. Despite the importance of water safety skills, aquaphobia remains a significant barrier to swimming competence among students worldwide. A comprehensive analysis of peer-reviewed studies (2018-2025) was conducted using PRISMA guidelines. Electronic databases (PubMed, ERIC, PsycINFO, Web of Science, Scopus) were searched to identify studies examining hydrotherapy interventions for school-aged participants with aquaphobia. Studies were included if they used experimental or quasi-experimental designs, reported quantitative outcomes, and focused on educational settings. Meta-analysis using random-effects models was conducted to calculate pooled effect sizes. Results showed that mindfulness-integrated hydrotherapy demonstrated highest effectiveness (g = 0.96), followed by cognitive-behavioral hydrotherapy (g = 0.83), adaptive aquatic programs (g = 0.79), virtual reality-assisted exposure (g = 0.72), and graded exposure therapy (g = 0.66). Interventions were most effective for younger children (5-8 years) and longer programs (≥12 weeks). These findings provide evidence-based recommendations demonstrating that mindfulness-integrated and cognitive-behavioral approaches are most effective for students with aquaphobia in educational settings.